Aproximación desde Michel Foucault a la transformación contemporánea del delito político en Colombia: de un mecanismo de normalización a un mecanismo de rechazo - Restrepo Orrego, Lucas Andrés (2023)
This article examines the notion of political crime in the co ntext of Colombia‘s current legal and political context. The author uses as a starting point the current perception of political crime in Colombia, as the understanding and application of this kind of crime were transformed. This paper shows how this trans formation has promoted new modes of subjection of rebellion through the punitive power. The proposed modes of subjection have had something in common: they attempt to approach rebelliousness from the liberal -procedural perspective, which is founded on vind icating the discourse of sovereignty as the only legitimizing instance of any form of punishment and political control. To justify the article‘s hypothesis, the author presents a vision of the problem of punitive subjection of rebelliousness based on Miche l Foucault‘s critique of the ―model of sovereignty.‖ The paper then shows how a certain legal -criminal discourse positioned political crimes as a mechanism of non -punitive normalization. Finally, the author analyzes a ruling of the Colombian Constitutional Court, opinion C- 456 of 1997, with the purpose of showing the way in which a new strategic position of political crime was consolidated.